Reading and Understanding in the Digital Age - A look at the critical need for close reading of digital and multimodal texts - Michael Manderino (Reading Today, 2015)
More than 200 million users share 60 million photos per month on Instagram. Meanwhile, 100 hours of video are uploaded to YouTube every minute, with more than six billion hours of video content viewed every month. Clearly, the proliferation of available images and videos highlights the visual nature of communication in the digital age. Digital texts are often referred to as multimodal because they make use of more than one mode of communication (e.g., text, image, sound, movement). Multimodal texts are also an integral part of classroom instruction. From picture books, maps, and photographs to newer practices such as 1:1 classroom environments and using instructional videos to “l ip the classroom,” teachers and students interact with multimodal texts for learning as well as entertainment and social media sharing.